Asymmetric Evolution and Expansion of the NAC Transcription Factor in Polyploidized Cotton - Fan, Kai; Li, Feng; Chen, Jiahuan; Li, Zhaowei; Lin, Weiwei; Cai, Size; Liu, Jianping; Lin, Wenxiong (Frontiers in Plant Science, 2018)
Polyploidy in Gossypium hirsutum conferred different properties from its diploid ancestor under the regulation of transcription factors. The NAC transcription factor is a plant-specific family that can be related to plant growth and development. So far, little is known about the NAC family in cotton. This study identified 495 NAC genes in three cotton species and investigated the evolution and expansion of different genome-derived NAC genes in cotton. We revealed 15 distinct NAC subfamilies in cotton. Different subfamilies had different gene proportions, expansion rate, gene loss rate, and orthologous exchange rate. Paleohexaploidization (35%) and cotton-specific decaploidy (32%) might have primarily led to the expansion of the NAC family in cotton. Half of duplication events in G. hirsutum were inherited from its diploid ancestor, and others might have occurred after interspecific hybridization. In addition, NAC genes in the At and Dt subgenomes displayed asymmetric molecular evolution, as evidenced by their different gene loss rates, orthologous exchange, evolutionary rates, and expression levels. The dominant duplication event was different during the cotton evolutionary history. Different genome-derived NACs might have interacted with each other, which ultimately resulted in morphogenetic evolution. This study delineated the expansion and evolutionary history of the NAC family in cotton and illustrated the different fates of NAC genes during polyploidization.